Correction to: Central line bundle including split-septum device and single-use prefilled flushing syringes to prevent port-associated bloodstream infections: a cost and resource-utilization analysis - İlker Devrim; Mustafa Taha Özkul; İlknur Çağlar; Yeliz Oruç; Nevbahar Demiray; Neryal Tahta; Canan Vergin (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.